2016
DOI: 10.1093/abbs/gmw026
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of resveratrol in combination with cisplatin on apoptosis via modulating autophagy in A549 cells

Abstract: Several studies have shown that combination treatment with natural products and chemotherapy agents can improve the sensitivity and cytotoxicity of chemotherapy agents. Resveratrol, a natural product, has many biological effects including antitumor and antiviral activities, as well as vascular protective effect. The aim of this study is to investigate the synergistic anticancer effect of resveratrol in combination with cisplatin and the potential anticancer mechanisms involved in A549 cells. The results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…We then investigated the molecular mechanism underlying this apoptotic pathway. Previous reports have suggested that resveratrol has the capability to induce autophagy and might also play a role in enhancing apoptosis [54][55][56]. However, our western blot results revealed that treatment with different concentrations of resveratrol increased LC3-II accumulation and decreased p62 expression levels in A549 cells, thus confirming the activation of complete autophagy flux by lysosomal degradation (Fig.…”
Section: Discussionmentioning
confidence: 41%
“…We then investigated the molecular mechanism underlying this apoptotic pathway. Previous reports have suggested that resveratrol has the capability to induce autophagy and might also play a role in enhancing apoptosis [54][55][56]. However, our western blot results revealed that treatment with different concentrations of resveratrol increased LC3-II accumulation and decreased p62 expression levels in A549 cells, thus confirming the activation of complete autophagy flux by lysosomal degradation (Fig.…”
Section: Discussionmentioning
confidence: 41%
“…Previous reports have suggested that resveratrol has the capability to induce autophagy and might also play a role in enhancing apoptosis [58][59][60]. However, our western blot results revealed that treatment with different concentrations of resveratrol increased LC3-II accumulation and decreased p62 expression levels in A549 cells, thus confirming the activation of complete autophagy flux by lysosomal degradation (Fig.…”
Section: Cytochrome C Translocation Through Mitochondrial Dysfunctionmentioning
confidence: 41%
“…For instance, although cisplatin is clinically effective, it lacks selectivity for tumor tissue, resulting in serious side effects, such as kidney-function damage, 101 neurotoxicity, 102 ototoxicity, 103 and the emergence of MDR, resulting in the failure of chemotherapy. 104 In addition, longterm or high-dose cisplatin treatment can also cause severe anemia. 105 Therefore, the clinical application of single drugs, such as cisplatin, has been greatly restricted.…”
Section: Antitumor Effects Of Tcmcombination Therapymentioning
confidence: 99%